Pilot study of pharmacist-assisted delivery of pharmacogenetic testing in a primary care setting. (October 2014) - Haga, Susanne B; Allen LaPointe, Nancy M; Cho, Alex; Reed, Shelby D; Mills, Rachel; Moaddeb, Jivan; Ginsburg, Geoffrey S
Aim: To describe the rationale and design of a pilot program to implement and evaluate pharmacogenetic (PGx) testing in a primary care setting.Study rationale: Several factors have impeded the uptake of PGx testing, including lack of provider knowledge and challenges with operationalizing PGx testing in a clinical practice setting.Study design: We plan to compare two strategies for the implementation of PGx testing: a pharmacist-initiated testing arm compared with a physician-initiated PGx testing arm. Providers in both groups will be required to attend an introduction to PGx seminar.Anticipated results: We anticipate that providers in the pharmacist-initiated group will be more likely to order PGx testing than providers in the physician-initiated group.Conclusion: Overall, we aim to generate data that will inform an effective delivery model for PGx testing and to facilitate a seamless integration of PGx testing in primary care practices.